Expert Investigations In Criminal Proceedings, Liability For Which Is Provided By Art. 345 Of Criminal Code Of Ukraine - Fedoryshchev, Ivan (Національний науковий центр «Інститут судових експертиз ім. Засл. проф. М.С. Бокаріуса», 2023)
The article considers importance of preserving and protecting the life and health of employees of the Security and Defense Forces, currently including law enforcement officers. The main types of expert research that should be conducted during the investigation of a crime, the responsibility for which is provided for in Art. 345 of Criminal Code of Ukraine, in particular, forensic medical one with involvement of forensic medical examiner a specialist in examination and investigative experiment; video and sound recording examinations; forensic psychological examination and a set of examinations, in case of the need for research in criminal proceedings of digital objects, telecommunications and computer forensic science, in case of receiving threats by a law enforcement officer or members of his family through means of communication. Importance of conducting forensic psychological examinations of law enforcement officers and their family members in order to receive compensation for the moral damage caused by the offense was emphasized. Importance of development and research of computer forensic science and research on digital objects, use of their capabilities during the investigation of the specified criminal offenses, etc. is argued.
Keywords: Forensic science , threat to law enforcement officer, forensic medical examination, examination, crime scene reconstruction, forensic video and audio analysis, forensic psychological examination, compensation for moral damage, research on digital objects, telecommunication examination, computer forensic science